Interview with Andriani Mitropoulou - Douvitsa, Ifigeneia; Henrÿ, Hagen (International Journal of Cooperative Law, 2024)
Thank you, Ms. Mitropoulou, for accepting this interview! It is my great pleasure to interview you with Hagen Henrÿ for our journal as your work has guided my research and enhanced my understanding of complex matters in cooperative law. As with the other interviewees may we start by asking what made you develop an interest in the subject of cooperative law and whether cooperatives in general, and cooperative law in particular, was part of your formal education.